Evaluation of urinary cyclohexanediols and cyclohexanol as biomarkers of occupational exposure to cyclohexane. Issue 4 (31st October 2015) - Takeuchi, Akito; Ogawa, Yoshihiro; Endo, Yoko; Kawai, Toshio; Namera, Akira; Yamamuro, Kenji; Sumino, Kimiaki; Endo, Ginji
Abstract : Evaluation of urinary cyclohexanediols and cyclohexanol as biomarkers of occupational exposure to cyclohexane: Akito Takeuchi, et al . Osaka Occupational Health Service Center, Japan Industrial Safety and Health Association Objectives: The aim of the present study was to comparatively evaluate the usefulness of urinary cyclohexanediols (CHdiols‐U) and cyclohexanol (CHol‐U) as biomarkers of occupational exposure to cyclohexane (CH). Methods: Sixteen subjects (14 men and 2 women) were exposed to CH during proof‐printing work. Personal exposure monitoring was conducted during the whole shift on the last working day of the week. The time‐weighted average level of exposure to CH (CH‐A) was measured using a diffusive sampler. Two urine samples were collected from each worker at different times during the same week: a baseline urine sample (before the first shift of the working week, after a 5‐day holiday with no CH exposure) and an end‐of‐shift urine sample (after the last shift of the same working week, the same day personal exposure monitoring was conducted). CH‐A, CHdiols‐U and CHol‐U were determined using a gas chromatograph‐flame ionization detector. Results: The CH‐A concentrations ranged from 4.5 to 60.3 ppm, with a geometric mean (GM) of 18.1 ppm. The GMs and ranges (in parenthesis) of the creatinine (cr)‐corrected end‐of‐shift 1, 2‐CHdiol‐U, 1, 4CHdiol‐U and CHol‐U concentrations were 12.1 (4.1−36.6), 7.5 (2.4−20.1) and 0.4 (0.2−1.0) mg/g cr, respectively. Both CHdiols‐U at the end of the shift were significantly correlated with CH‐A (correlation coefficients for 1, 2‐CHdiol‐U and 1, 4‐CHdiol‐U of 0.852 and 0.847, respectively). No correlation was observed between CH‐A and CHol‐U. Conclusions: CHdiols‐U at the end of the last shift of the working week are suitable biomarkers of occupational exposure to CH, but CHol‐U is not suitable.